A comprehensive atlas of full-length Arabidopsis eccDNA populations identifies their genomic origins and epigenetic regulation. - Syed Shan-E-Ali Zaidi; Sara Shakir; Hanne De Kort; Devang Mehta; Vu Nguyen; Ruben Gutzat; Hervé Vanderschuren (PLoS Biology)
Extrachromosomal circular DNA (eccDNA) has been described in several eukaryotic species and has been shown to impact phenomena as diverse as cancer and herbicide tolerance. EccDNA is thought to arise mainly through transposable element (TE) mobilization. Because studies based on short-read sequencing cannot efficiently identify full-length eccDNA forms generated from TEs, we employed the CIDER-Seq pipeline based on long-read sequencing, to obtain full-length eccDNAs from Arabidopsis. The generated eccDNA datasets identified centromeric/pericentromeric regions as hotspots of eccDNAs with several eccDNA molecules originating from Helitron and LTR TEs. To investigate the role of epigenetic marks on TE-derived eccDNA biogenesis, we studied Arabidopsis methylation mutants dcl3, rdr6, ros1, and ddm1. Contrasting the TE-suppression previously reported in the hypermethylated ros1 mutants, we identified activation of TEs in ros1, specifically of LTR/Gypsy TEs. An enrichment of LTR/Copia elements was identified in actively dividing calli and the shoot apical meristem (SAM). Uncharacterized "variable TEs" with high eccDNA and expression were identified in the SAM, including ATCOPIA58. Together, our study reveals the genomic origins of eccDNAs and delineates the link between epigenetic regulation, transposon mobilization, and eccDNA biogenesis.